lncRNA HIF1A-AS2 acts as an oncogene to regulate malignant phenotypes in cervical cancer - Liu, Yang; Zhang, Yunyan; Chen, Cha; Roy, Bhaskar; Li, Qun; Zhang, Wei; Zhang, Xuan; Pu, Jieying; Li, Yuguang; Liu, Yanli; Liao, Huanlan; Wang, Jingjing; et al. (Frontiers in Oncology, 2025)
BackgroundLong noncoding RNAs (lncRNAs) HIF1A-AS2 is upregulated in multiple human cancers and are associated with various aspects of tumor progression. However, the molecular mechanisms of HIF1A-AS2 in cervical cancer (CC) remain largely unknown. In this study, we aim to investigate the expression pattern and signaling pathways of HIF1A-AS2 in CC.MethodsThe study included a group of 20 CC patients, from whom tumor tissue specimens were collected. Additionally, three distinct CC cell lines (HeLa, SiHa, CaSki) were utilized. Quantitative real-time PCR (qRT-PCR) was used to assess the transcript levels of HIF1A-AS2 in these samples. Functional studies were performed by CCK-8, Transwell and Apoptosis assays. Databases including JASPAR, miRDB and Targetscan were used for the transcription factor or target miRNA prediction, subsequent dual luciferase activity assay, chromatin immunoprecipitation (ChIP) and Ago2 immunoprecipitation (RIP) were also adopted for validation.ResultsThe study demonstrated that HIF1A-AS2 expression was elevated in clinical cervical cancer specimens and cultured cell lines in comparison to normal controls. Knockdown of HIF1A-AS2 notably inhibited the proliferation and invasion of cervical cancer cells, while inducing apoptosis. In contrast, HIF1A-AS2 overexpression promoted cellular proliferation and invasion and suppressed apoptosis. It was also identified that c-Jun functions as a transcription factor, activating HIF1A-AS2 expression. Additionally, HIF1A-AS2 was found to serve as a molecular sponge for miR-34b-5p, negatively regulating its expression. Furthermore, HIF1A-AS2 controlled the expression of radixin (RDX) by sponging the miR-34b-5p pathway.ConclusionOur findings indicate that c-Jun-activated HIF1A-AS2 acts as an oncogenic factor in CC by sponging miR-34b-5p to target radixin. These findings suggest that HIF1A-AS2 might be a viable and promising therapeutic target for cervical cancer treatment.